ICT aided citizenry participation: a pragmatic adoption of mobiles phones to support voter education in Africa - Gitau, Silvian Wanjiku (Department of Computer Science, 2024)
The United Nation's Millennium declaration touts democracy as the pre-requisite to economic development. However, very little work has been done in the use of technology to advance democracy in developing countries and especially in Africa. On the other hand, a lot of effort has been put into place to bridge the digital divide in these developing countries by introduction of technologies best suited for the environment. Key among the new technologies is the mobile phone. This study outlines a project that is based on partnerships with Non-Governmental Organizations (NGOs) specifically working on democratic communication in Kenya and South Africa. In particular we sought to empower these NGOs by increasing their capacity in voter education through using mobile phones as a voter education tool. Voter education is a complex process that takes into account various factors such as voter demographic information, transparency, universality in reach, channel and medium of use and, most importantly, the timing has to be right. These requirements are compounded by challenges in the African context, including: lack of telecommunication infrastructure; high illiteracy; incidences of violence and vandalism mainly during an electioneering period. We introduce the Big Board, a public information system that compliments mobile phones in the dissemination of multi-media information by the elimination of connection charges by mobile service providers, whilst providing a means to provide local content in remote areas without the need for an Internet connection. A key finding at the end of this study was the importance of pragmatism when approaching the design of technology for developing world. By taking into account environmental factors we were able to engage in mutually beneficial partnerships between us as technologist NGOs. Whereas we provided a means through which mobile phones could be used for voter education, they provided us with the information on voter education and democracy as well as a means to measure the impact of this tool using their own evaluation techniques.